PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Prastika, Indri Wahyu; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACT The purpose of this research is to examine the influence of financial performance which is measured by return on equity (ROE), debt to equity ratio (DER), the dividend policy is measured by dividend payout ratio (DPR), the investment decision is measured by price earnings ratio (PER), and the firm size is measured by the natural log (Ln) of the total assets of the firm value is measured by price book value (PBV). The population is all consumer goods industry manufacturing company sector listed in Indonesia Stock Exchange. The sample collection technique has been done by using purposive sampling technique. Based on the predetermined criteria 16 companies during the period of 2013 to 2015 with the observation of data as many as 48 have been obtained as samples. The analysis method has been done by using multiple linear regression analysis. The result of this research indicates that profitability and the investment decision give influence to the firm value. Whereas leverage, dividend policy, and Firm size does not give any influence to firm value.Keywords: Financial performance, dividend policy, investment decision, firm size, firm value.